In vivo components analysis of Shenhua tablets active in IgA nephropathy - Huiqiang Liu; Ping Li; Fengting Yin; Hui Sun; Ying Zheng; Chang Liu; Xiangmei Chen; Xiaotong Yan; Xijun Wang (Elsevier, 2024)
Introduction: Shenhua Tablet (SH), a traditional Chinese medicine (TCM) formulation with seven herbs, is widely used in the clinical treatment of Immunoglobulin A (IgA) nephropathy. Despite its effectiveness, the specific active components of SH in vivo remain unidentified, presenting a challenge for further research on its pharmacodynamic material basis. Methods: A rat model of IgA nephropathy was treated with Shenhua Tablet (SH) to evaluate its potential in protecting kidney function. UHPLC-Q/Orbitrap/LTQ MS was utilized to identify active components of SH in vivo under the active condition for intervening IgA. Results: SH significantly ameliorated Thy-1 antibody-induced IgA nephropathy by decreasing glomerular injury, suppressing pro-inflammatory factor secretion, and inhibiting mesangial cell proliferation. 83 kinds of prototypal compounds absorbed into the blood were comprehensively characterized, along with 145 metabolites arising from Phase I and Phase II metabolic reactions. and the metabolic pathways of these metabolites were elucidated for the first time. 10 active components were found to be correlated with the effectiveness of SH, including Atractylenolide I, chlorogenic acid, ferulic acid, salidroside+SO3, calycosin+O, furanodiene, paeoniflorin-H2, germacron+O, formononetin+C6H8O6, and calycosin. Discussion: The results fill the current research gap on the active components of SH and examine its potential renoprotective effects on IgA nephropathy. This study provides valuable references and insights for elucidating the active components and mechanisms of action of SH in treating IgA nephropathy.